The Influence of Price Perception and Brand Image on People’s Purchasing Decisions Regarding Electric Cars in DKI Jakarta - Ambarwati, Ambarwati; Pratomo, Djoko; Utomo, Dimas Ahdaharish (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2026)
This study examined the impact of price perception and brand image on electric vehicle purchase decisions in DKI Jakarta. A quantitative research design was employed using multiple linear regression analysis, with data processed through SPSS. The findings revealed that price perception and brand image had a significant effect, both partially and simultaneously, on purchase decisions. These results suggested that effective pricing strategies and strong brand positioning played a crucial role in encouraging the adoption of electric vehicles. This study provided practical insights for automotive manufacturers and marketers in formulating strategies to enhance consumer purchase decisions in emerging electric vehicle markets.